FIRST RECORD OF LERNAEA CYPRINACEA (COPEPODA) IN A NATIVE FISH SPECIES FROM A BRAZILIAN RIVER - costa, Aline Angelina A (2013)
This is the report of the occurrence of Lernaea cyprinacea (Linnaeus, 1758) parasitizing the native fish species Steindachnerina insculpta (Fernández-Yépez, 1948). Sixty host specimens were captured in Taquari River, municipality of Taquarituba, São Paulo State, Brazil. Three hosts were infested with L. cyprinacea. The infestation rate was low, with one parasite per host. Proper management should be applied in fish farms to prevent the escape of this parasite, and its consequent spread.